Maintenance management at indoor stadium / Muhamad Ariff Mohamad Abu Sadin - Mohamad Abu Sadin, Muhamad Ariff (Faculty of Architecture, Planning and Surveying, 2013)
Maintenance is work that is carried out to preserve an asset such as roof, door, roof, in order to enable its continued use and function, above a minimum acceptable level of performance, over its design service life without unforeseen renewal or major repair activities. Maintenance is the important thing for any building or space to make sure that the property asset is valuable in another year and coming soon. So the indoor stadium is also requiring having maintenance aspect to get the benefits as mention above. Through by a good management, it becomes more efficient for the indoor stadium.This dissertation are to investigate on maintenance operation had been apply by indoor stadium management and management of organization for three indoor stadium. There are Indoor Stadium Melawati, Indoor Stadium National Bukit Jalil, and Indoor Stadium Nilai.